A ocupação do Bronze Final do Centro Histórico de Oeiras: os materiais da Rua das Alcássimas - Cardoso, João Luís (2017)
In this paper we present Late Bronze materials recovered at the Historic Center of Oeiras. This large assemblage of plain and decorated containers, the last with the technique of “burnished ornaments” is associated with denticulated sickle’s flint flakes and an ivory comb. These findings are discussed within the framework of the Late Bronze Age society of the region on or of the north bank of the mouth of the Tagus, dating from the earliest trade contacts with the Central and Eastern Mediterranean of the beginnings of the first millennium BC.